Impacts of Translocation on Nigerian International Students' Eating Habits in Northern Cyprus - Onyeama, Anthony E.; Ersoy, Ergin; Ndukauba, Precious C. (Star Scholars Network, 2023)
Generally, translocation is never without complaints or crises, especially when moving from one country to another. International students are a lucrative segment of global tourism. However, the ripple effect of translocation affects their eating habits. Despite the abundance of studies on translocation in animal and plant sciences, literature on the impacts of translocation on international students' eating habits is scarce. This study explores the impacts of translocation on Nigerian international students' eating habits in Northern Cyprus. This qualitative case study used semistructured interviews to collect data from 13 students at Eastern Mediterranean University, North Cyprus. The findings reveal three themes characterizing their experiences: motivational, economic, and physiological factors. Voyat analysis shows that the major factors affecting their eating habits are eating, food choice, new environment, and time differences. This study contributes to the education and tourism literature. Implications, limitations, and future research are discussed.
Keywords: Eating habits; international students; translocation; spillover effect theory; Northern Cyprus